2011
DOI: 10.1111/j.1447-0756.2010.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgens and sexual dysfunction in naturally and surgically menopausal women

Abstract: Our findings suggest that while surgical menopause is detrimental to sexual functioning by itself, lower testosterone levels are predictive of sexual dysfunction, especially in naturally menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…Palacios et al91 found that examining the sexual history of postmenopausal women since fertility age is the first step in diagnosing and treating postmenopausal women with sexual dysfunction, which is consistent with the results of the studies which correlated sexual function with the number of pregnancies and childbirth 35. Regarding hormonal treatment, it seems that the hormone administration and its onset are effective in the level of sexual function 92. As it was already mentioned, some studies have shown the protective effect of hormone therapy on sexual function 4546…”
Section: Discussionmentioning
confidence: 65%
“…Palacios et al91 found that examining the sexual history of postmenopausal women since fertility age is the first step in diagnosing and treating postmenopausal women with sexual dysfunction, which is consistent with the results of the studies which correlated sexual function with the number of pregnancies and childbirth 35. Regarding hormonal treatment, it seems that the hormone administration and its onset are effective in the level of sexual function 92. As it was already mentioned, some studies have shown the protective effect of hormone therapy on sexual function 4546…”
Section: Discussionmentioning
confidence: 65%
“…On the other hand, some studies mentioned the role of hormones in sexual response ( 47 ). It was shown that titer of serum testosterone in post- menopausal women is associated with sexual function ( 48 , 13 , 49 ). Also, low sexual desire, arousal and lubrication are related to low androgen level ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alarslan'ın yaptığı çalışmada Amerika'da premenopozal dönemde uyarılma ve lubrikasyon problemi olan kadınların, olmayan kadınlara göre menopozal dönemde depresyon semptomlarını daha fazla yaşadığı belirtilmiştir. 33 Yangın ve ark. 'nın yaptıkları çalışmada çalışmamıza benzer şekilde lubrikasyon ve ağrı problemleri azaldıkça depresyonunda azaldığı saptanmıştır.…”
Section: Discussionunclassified